Prioritizing Integrated Marketing Communication Tools in Sport Tourism in Iran Based on ACCA Model - Esmaeili, Narges; Ashraf Ganjuei , Farideh; Tojari, Farshad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  This study aims to prioritize the Integrated Marketing Communication (IMC) tools in the sports tourism sector in Iran based on the ACCA model to enhance the effectiveness of marketing strategies and attract more tourists.Methods and Materials: A descriptive-field research method was employed to achieve the study's objectives. Data were collected through a researcher-made questionnaire administered to a statistical population comprising 53 experts and specialists in sports management, all holding at least a master's or doctoral degree in the field. The Analytical Hierarchy Process (AHP) was used as the data analysis method to determine the weight and priority of IMC tools. The study ensured consistency in responses by calculating the inconsistency rate for paired comparisons, ensuring it remained below the acceptable threshold of 0.1.Findings: The results revealed that advertising and public relations hold the highest importance in creating awareness within the sports tourism sector, with television advertising ranking the highest among advertising tools. Sales promotion emerged as the most significant tool for developing comprehension, with discount coupons receiving the highest final weight. For fostering conviction, personal selling and direct marketing were found to be the most influential, with presence selling and catalog distribution identified as the most effective methods. Finally, in the action stage, personal selling and direct marketing remained the most impactful tools, highlighting their significance in converting potential tourists into actual customers.Conclusion: The study concludes that an effective IMC strategy in sports tourism should prioritize advertising and public relations to build awareness, followed by sales promotion for comprehension and personal selling for conviction and action. These findings provide valuable insights for tourism authorities and marketers in Iran to allocate resources more efficiently and optimize communication strategies to boost the country's sports tourism industry.